The Influence Of Financial Literacy On Investment Decisions Of Generation Z In Maros Regency (Case Study Of Generation Z In Lau District) - Annisa Dewi Lebbi; Tenri Sayu Puspitaningsih Dipoatmojo; Hety Budiyanti (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
: Generation Z in the digital era has easy access to various investment instruments, but differences in financial literacy levels often affect the quality of their investment decisions. This study aims to examine the extent to which financial literacy influences investment decisions among Generation Z in Lau District, Maros Regency. This study used a quantitative approach with a survey method, in which 60 respondents were selected through a purposive sampling technique. Data were collected using a questionnaire with a Likert scale, then analyzed through a series of statistical tests including validity, reliability, normality, heteroscedasticity, and simple linear regression. The results of the study show that financial literacy has a positive and significant influence on investment decisions, with a correlation coefficient (R) of 0.991 and a determination coefficient (R²) of 0.983. This indicates that 98.3% of the variation in investment decisions can be explained by financial literacy. These findings confirm that the better an individual's level of financial literacy, the more rational and appropriate investment decisions they make. Practically, these results emphasize the importance of improving financial literacy among the younger generation to encourage intelligent, rational, and long-term goal-oriented investment behavior, especially in areas with varying levels of financial literacy, such as Lau District.